Introducing Children to Allah: Developing Religious Spirit in Elementary School Through Teaching Tawheed at Home - Noven Kusainun; Suhairee Berngacha (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2023)
This article discusses how to introduce children to Allah and how to develop their religious spirit during their childhood, specifically during their time in primary school. The author emphasizes the importance of educating children about Allah and building their faith early on. This research is a literature review study on teaching children about tawheed (oneness of God) within the family setting. The method used in this research is content analysis. The analysis is conducted on several aspects: the command to educate children about tawheed, the primary role of parents in education, and the method of teaching tawheed to children. Parents should explain to their children that everything in the universe exists because Allah created it and provide simple analogies to help children understand the concept. Additionally, parents should strive to develop their children's religious spirit by creating an Islamic atmosphere in the household, teaching them good speech, taking them to the mosque, and using school holidays to participate in religious activities. The author highlights that these efforts should be ongoing and consistent throughout the child's upbringing.